Um Modelo para o Desenvolvimento de Aplicações Web Acessíveis - Maia, Lucinéia Souza; Turine, Marcelo Augusto Santos; Sandim, Hércules da Costa; Paiva, Débora Maria Barroso (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
The Internet is an important mean of information transmission, of interaction between people, accomplishment business-oriented, education and government services. However, problems related to accessibility content have been a factor for exclusion of users, mainly those with some type of disability. Such process of exclusion has motivated research for methods, techniques and tools to offer to the Web professional sustentation for development of accessible Web applications. In this context, this work presents a Accessibility Tasks Model (MTA) inserted in ISO/IEC 12207 Development Process (Standard for Information Technology – Process of Software Life Cicle) to assist analyze, design, implementation, and evaluation of accessible software. Pantaneiro framework is presented to support sub process in MTA. It was modified to produce Web pages with standard of Web accessibility. To test, evaluate and validate the MTA and accessible Pantaneiro, and to evaluate the strategy to promote the accessibility, one case study was elaborated with groups of developers.